Antagonistic roles of Drosophila Tctp and Brahma in chromatin remodelling and stabilizing repeated sequences - Hong, Sung-Tae (Nature Publishing Group, 2016)
Genome stability is essential for all organisms. Translationally controlled tumour protein (TCTP) is a conserved protein associated with cancers. TCTP is involved in multiple intracellular functions, but its role in transcription and genome stability is poorly understood. Here, we demonstrate new functions of Drosophila TCTP (Tctp) in transcription and the stability of repeated sequences (rDNA and pericentromeric heterochromatin). Tctp binds Brahma (Brm) chromatin remodeler to negatively modulate its activity. Tctp mutants show abnormally high levels of transcription in a large set of genes and transposons. These defects are ameliorated by brm mutations. Furthermore, Tctp promotes the stability of repeated sequences by opposing the Brm function. Additional regulation of pericentromeric heterochromatin by Tctp is mediated by su(var)3-9 transcriptional regulation. Altogether, Tctp regulates transcription and the stability of repeated sequences by antagonizing excess Brm activity. This study provides insights into broader nuclear TCTP functions for the maintenance of genome stability.